EFFECT OF KNOWLEDGE SHARING ON EMPLOYEE PERFORMANCE THROUGH INNOVATION - Setiawan, Temmy (Journal of Industrial Engineering & Management Research, 2019)
The development of organization in the era of globalization is shown by the development of human resources to support knowledge-based activity. The importance of knowledge resources as a intellectual capital in the advancement of the company. This research aims to examine and to analyze whether knowledge sharing affects employee performance through innovations , with a saturated sampling technique with a sample of 230 respondents used SEM SmartPLS 2.0 analysis techniques. The results showed that the 1) knowledge sharing on employee performance is a positive and significant, 2) a positive and significant of knowledge sharing on innovation, 3) innovation on employee performance is a positive and significant, 4) innovation does not mediate the effect of knowledge sharing on employee performance.